The role of the value added by the venture capitalists in timing and extent of IPOs - Tereza Tykvová (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
We analyze the venture capitalist's decision on the timing of the IPO, the offer price and the fraction of shares he sells in the course of the IPO. A venture capitalist may decide to take a company public or to liquidate it after one or two financing periods. A longer venture capitalist's participation in a firm (later IPO) may increase its value while also increasing costs for the venture capitalist. Due to his active involvement, the venture capitalist knows the type of firm and the kind of project he finances before potential new investors do. This information asymmetry is resolved at the end of the second period. Under certain assumptions about the parameters and the structure of the model, we obtain a single equilibrium in which highquality firms separate from low-quality firms. The latter are liquidated after the first period, while the former go public either after having been financed by the venture capitalist for two periods or after one financing period using a lock-up. Whether a strategy of one or two financing periods is chosen depends on the consulting intensity of the project and / or on the experience of the venture capitalist. In the separating equilibrium, the offer price corresponds to the true value of the firm.
urn:nbn:de:hebis:30-10308
Keywords: D80; G24; G32; 330; Venture Capital; IPO; Lock-up; Timing